Agricultural commodity projections, 1970-1980 : volume 1, part I: General outlook; part II: projections by commodity - Food and Agriculture Organization of the United Nations (Rome : Food and Agriculture Organization of the United Nations, 1971)
The present study is essentially a continuation of earlier FAO studies on commodity projections. The basic approach remains the same, but the number of countries studied has increased by 33, and fishery products, oilcakes, wine and hides and skin have been added to the projection commodities
Vol.1
Includes bibliographical references.
mf24/01/2019
Loans
Keywords: Produce trade